Effect of internal cooling/heating coil on adsorption/regeneration of solid desiccant tray for controlling air humidity - B. N. Hung (2018)
Thermal performances of solid desiccant tray having internal cooling/ heating coil for air humidity adsorption and desiccant regeneration are investigated. Three units of desiccant tray each of 48 cm × 48 cm cross-sectional area and 2.5 cm thickness filled with silica gel are tested in a wind tunnel. For adsorption process, an air stream is flowing through the desiccant trays and the air humidity is captured by the silica gel. Approximately 10-40% of air humidity could be adsorbed more in case of the internal cooling. Besides, the outlet air temperature increases only slightly. In regeneration process, a hot air stream is used to repel the moisture in the silica gel. With the internal heating, the regeneration time is shorter compared with that without internal water heating. In addition, a correlation for calculating the adsorption/regeneration performance of the silica gel trays is developed and the results from the model agree well with the experimental data. Copyright © 2008 John Wiley & Sons, Ltd.